Double balloon enteroscopy: Effective and minimally invasive method for removal of retained video capsules. Issue 5 (26th February 2014) - Makipour, Kian; Modiri, Alexandra N.; Ehrlich, Adam; Friedenberg, Frank K.; Maranki, Jennifer; Enestvedt, Brintha K.; Heller, Steven; Tokar, Jeffrey; Haluszka, Oleh
<x xml:space="preserve">Abstract</x> Background and Aim Prior case series document removal of retained video capsules predominantly via surgical intervention. Data on endoscopic removal of retained capsules are limited. Our aim was to describe an endoscopic method of retrieval using double balloon enteroscopy (DBE). Methods A retrospective case series examination found 10 patients who underwent DBE for retrieval of a retained video capsule at two large tertiary referral academic centers from May 2007 to June 2013. Results Mean age of patients was 64.9 ± 18.1 years (four females, six males). Five patients failed to pass the capsule as a result of an ileal or jejunal stricture (one patient with ulcerative colitis; four patients with Crohn's disease); two patients had a small bowel stricture as a result of non‐steroidal anti‐inflammatory drug enteropathy; one patient had intermittent partial small bowel obstruction without evidence of a stricture; one patient had an obstructing malignant jejunal mass and one patient had a small bowel stricture as a result of radiation enteritis. Endoscopic removal via DBE was successful in eight of 10 patients (80%). The remaining two patients underwent surgical removal of the retained capsule. The two failed cases of capsule retrieval were both patients with suspected ileal disease. Conclusions The most common cause of capsule retention was underlying Crohn's disease. DBE is an effective and minimally invasive method of capsule retrieval, including those patients with ileal disease, which has not been previously described. DBE can prevent unnecessary surgery while providing endoscopic therapy of inflammatory strictures by dilation.